The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1097/00006534-200007000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Therapy after Immediate Breast Reconstruction with Implants

Abstract: The use of implants in immediate breast reconstruction is presently a common option. However, the practice should be evaluated in consideration of possible adjuvant therapies needed to control disease and to rule out negative interactions. This article discusses the effects of radiotherapy on breast implants with regard to the final cosmetic result. Six out of 124 cases of immediate breast reconstruction with implants were followed and evaluated in terms of capsular contracture and final aesthetic result after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0
5

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(33 citation statements)
references
References 8 publications
1
27
0
5
Order By: Relevance
“…Radiotherapy inevitably damages the tissue, and, as long as the modus of radiotherapy is unchanged, post-radiation breast reconstruction will be more challenging. Most studies find that radiotherapy in an implant-based reconstruction increases complications and late failure rates (5,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). The results of the present study are in line with those of other studies in this field (5,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)30,31,33).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Radiotherapy inevitably damages the tissue, and, as long as the modus of radiotherapy is unchanged, post-radiation breast reconstruction will be more challenging. Most studies find that radiotherapy in an implant-based reconstruction increases complications and late failure rates (5,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). The results of the present study are in line with those of other studies in this field (5,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)30,31,33).…”
Section: Discussionsupporting
confidence: 91%
“…In the majority of studies, radiotherapy is shown to adversely affect outcome after implant-based breast reconstructions, with increased late failure rates (5,11,12), poor aesthetic results, loss of symmetry (13)(14)(15), capsular contracture, and infection, even when using the latest generation of implants (5,11,12,14,(16)(17)(18)(19)(20)(21)(22)(23)(24).…”
Section: The Effect Of Radiotherapy On Breast Reconstructionmentioning
confidence: 99%
“…Techniques have evolved since that time and today comprise the use of prosthetic materials, autologous tissue, or a combination thereof [12]. The cosmetic outcome of reconstruction with implant after postoperative radiotherapy is not always satisfactory because of capsular contracture and skin changes due to irradiation [13]. For that reason, Petit et al [14] suggested the concept of NSM followed by intraoperative radiotherapy and immediate reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…These complications include pain, infection, implant rupture, wound dehiscence or implant exposure, implant migration, contractures, and, occasionally, a need for implant removal [1,8,9,38,42,47,[50][51][52]. Also, the rate of patients satisfaction with cosmetic outcome ranged widely from 7% to 88%, as compared to 64% to 97% in non-irradiated patients [6,8,40,[44][45][46][47][48]51,53]. The major primary cause of unfavorable cosmetic results in these cases is capsular contracture [1,9,38,42,43,52,54], which is possibly attributed to subclinical infections, hemorrhage, and radiation fibrosis [42,55].…”
Section: Irradiation and Prosthetic Breast Reconstructionmentioning
confidence: 99%